Sustainability of the Youth Olympic Games - Edes, A. (University of Peloponnese, 2021)
2020 marked the 10-year anniversary of the first ever Youth Olympic Games (YOG). On this occasion, the research overviewsthe 10 years of the YOG, focusing on the sustainability of the event with specific examples from the six editions held so far and from the concept itself. Sustainability is a significant issue at every major sports event; the long-term success is defined by the sustainability of the event concept and the specific sustainable solutions in social, environmental, and economic areas. Based on the available literature on the three summer and three winter editions held between 2010 and 2020, the study draws a detailed picture with several examples on the comprehensive sustainability in terms of social, environmental, and economic aspects, listing both the positive and negative findings. The research findings show that the YOG has a significant focus on sustainability. The sustainability elements are embedded in every step from the bidding phase through the planning all the way through the implementation. It is also highlighted by the International Olympic Committee (IOC) in the Candidature Procedure and Questionnaire, and the evaluation of the bidding cities is made with remarkable attention on the sustainability concept of the bid. The intention and efforts of the IOC and the host cities to organise the Games in a sustainable way and leave a positive legacy can be clearly seen. However, what is beyond the implementation of the YOG and what happens after the event is more unclear. The long-term effect on the young people`s life and on the locals is not well researched yet. There are very positive feedbacks on the Learn & Share program, the sports program and on the whole event as well, but some research show negatives feedbacks too. As the YOG is still considered to be a "young" event, with having only six editions held, there is a lot of room for development and for further research on the topic to ensure a sustainable future for the YOG within the Olympic Movement.